Synthesis and Antibacterial Activity of Some Chalcones and 1,4-Oxazipine Derivatives - Bharucha, P.B.; Naik, H.B. (Asian Journal of Chemistry, 2010)
Some new 1,4-oxazipine derivatives have been prepared by condensation of 2',4'-dichloro-5'-fluorochalcones with 2-amino ethanol in ethanol. The structures of the products have been characterised by elemental analysis and IR spectral studies. The products have been screened for antibacterial activity against Staphylococcus aureus and Escherichia coli.